The excitation of CO in CO-dominated cometary comae. Issue 3 (25th January 2023) - Żółtowski, M; Lique, F; Loreau, J; Faure, A; Cordiner, M
ABSTRACT: An abundance of CO significantly surpassing the abundance of H2 O is observed in the comae of comets at large heliocentric distances. In these environments, CO molecules can be the most abundant species and they may be therefore the dominant projectiles inducing collisional excitation of the cometary molecules. It is thus of high interest to investigate the excitation of CO by CO. This article provides a new set of CO–CO collisional rate coefficients for temperatures up to 150 K and for CO rotational levels j 1 up to 10. These data are obtained from quantum scattering calculations using the coupled states approximation. They are used in a simple radiative transfer model in order to test their impact on the excitation of cometary CO. Because mutual (de-)excitations of the target and projectile are important, the CO projectile was assumed to be thermalized at the kinetic temperature. We found that the non-local thermodynamical equilibrium regime extends for CO densities in the range 10 3 –10 7 cm −3 . We also observed that as soon as the CO/H2 O ratio is larger than 70 per cent/30 per cent, the contribution of H2 O collisions can be neglected. Similarly, the excitation of CO by CO may be ignored for relatively low CO/H2 O density ratios (≤30 per cent/70 per cent). Finally, when the coma is a ∼50 per cent/50 per cent mixture of CO and H2 O, the contribution of both colliders is similar and has to be considered.